2021
DOI: 10.3389/fmicb.2021.714409
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs, the Link Between Dengue Virus and the Host Genome

Abstract: Dengue virus (DENV) is a small envelope virus of Flaviviridae that is mainly transmitted by Aedes aegypti and Aedes albopictus. It can cause dengue fever with mild clinical symptoms or even life-threatening dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). At present, there are no specific drugs or mature vaccine products to treat DENV. microRNAs (miRNAs) are a class of important non-coding small molecular RNAs that regulate gene expression at the post-transcriptional level. It is involved in and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 107 publications
(163 reference statements)
0
8
0
Order By: Relevance
“…The in vitro study of IAV shows the increased expression level of miR-132 and target MAPK3/ERK1 which involved in TLR, MAPK pathway ( Buggele et al, 2012 ). The miR-30 family members are involved in the regulation of immune signaling pathways during different virus infections such as IAV, and flaviviruses (DENV, Zika virus) ( Carvalho-Silva et al, 2022 ; Su et al, 2021 ). The cell lines (HeLa, U937) infected with DENV shows increased expression of miR-30e* which target IκBα which is an inhibitor of NF-κB and activates the NF-κB pathway, hence promoting expression of IFN-ꞵ and its downstream IFN stimulated genes such as MxA, OAS1, IFITM1 which inhibit the virus replication ( Su et al, 2021 ; Zhu et al, 2014a ).…”
Section: Host Non-coding Rnas- Potential Role In the Regulation Of Csmentioning
confidence: 99%
“…The in vitro study of IAV shows the increased expression level of miR-132 and target MAPK3/ERK1 which involved in TLR, MAPK pathway ( Buggele et al, 2012 ). The miR-30 family members are involved in the regulation of immune signaling pathways during different virus infections such as IAV, and flaviviruses (DENV, Zika virus) ( Carvalho-Silva et al, 2022 ; Su et al, 2021 ). The cell lines (HeLa, U937) infected with DENV shows increased expression of miR-30e* which target IκBα which is an inhibitor of NF-κB and activates the NF-κB pathway, hence promoting expression of IFN-ꞵ and its downstream IFN stimulated genes such as MxA, OAS1, IFITM1 which inhibit the virus replication ( Su et al, 2021 ; Zhu et al, 2014a ).…”
Section: Host Non-coding Rnas- Potential Role In the Regulation Of Csmentioning
confidence: 99%
“…Several studies have identified miRNAs that are targets of cellular genes important to flavivirus infections ( Su et al., 2021 ; Polonio and Peron, 2021 ), but these viruses can also generate noncoding RNAs with important functions in replication and pathogenesis, such as sfRNAs and viral miRNAs (vmiRNAs). Such noncoding RNAs are not the aim of this review; for more information, we suggest to the readers the excellent review by Clarke et al.…”
Section: Mirnas With a Target In The Flavivirus 3’utrmentioning
confidence: 99%
“…The 11 kb genome consists of three structural proteins, seven non structural proteins and 3’ and 5’ untranslated region. The three structural proteins consist of C protein, prM/M protein and E protein while the seven non-structural ones are NS1, NS2A, NS2B, NS3, NS4A, NS4B and NS5 7 . E protein is a large cysteine rich structural protein having 495 amino acids mainly responsible for host cell binding and entry 8 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The viral pathogen is also spilled over to epidermis and dermis where several dendritic cells like Langerhans and keratocytes are infected 14 15 . Dengue virus enters the cell primarily by clathrin mediated endocytosis where E protein is bound to multiple membrane receptors like heparin sulphate 16 , dendritic cell-specific intracellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) 7 17 . The E protein gets converted from dimeric to trimeric state when shifted from alkaline condition of cell surface to acidic condition of endosome.…”
Section: Introductionmentioning
confidence: 99%